Facing the missile challenge : U.S. strategy and the future of the INF Treaty - Kearn, David W. (RAND, 2012)
The Intermediate Nuclear Forces Treaty (INF), signed in 1987, eliminated nuclear and conventional ground-launched ballistic and cruise missiles with ranges between 500 and 5,500 kilometers from the United States and Soviet arsenals. The treaty was a diplomatic watershed, signaling the beginning of the end of the Cold War, and has served as a basis for security and stability of Europe. However, the security environment has changed dramatically in the past twenty years. To develop and deploy a new generation of land-based intermediate-range ballistic missiles, the United States would have to withdraw from the Treaty. Such an action would have significant political and military implications. The study attempts to explore and illuminate some potential responses of critical international actors, such as Russia, China, and America's NATO and East Asian allies, to fully understand the expected costs that may be incurred over time. The study concludes with a consideration of potential ways forward for the United States to provide policymakers with guidance on how to proceed in both diplomatic and political-military terms to best address the missile-proliferation threat.